Boston Marathon - Wiseman, Blaine (Sporting championships, 2011)
"Each year, runners from around the world travel to Boston to compete in the most-recognized annual marathon in the world. The Boston Marathon is considered one of the world's greatest fitness challenges."--Back cover.